2019
DOI: 10.1007/s11356-019-05889-2
|View full text |Cite
|
Sign up to set email alerts
|

Waste-activated sludge disruption by dry ice: bench scale study and evaluation of heat phase transformations

Abstract: The freezing process consists of dissipating heat from the product until the final temperature is lower than the temperature of crystallisation of that product. Freezing can be used for numerous applications, including for disruption of waste-activated sludge (WAS). The aim of this study was to calculate the estimated amount of heat conveyed between the solidified carbon dioxide and the WAS, in the following ratios: 0.25:1; 0.5:1; 0.75:1 and 1:1. In heat of phase transformations, dry ice sublimation, water sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…(2019) [34], the COD content in the dissolved phase increased to 205 mgO 2 /dm 3 at a SCO 2 /SAS volumetric ratio of 0.25 and peaked at 889 mgO 2 /dm 3 at a SCO 2 /SAS ratio of 1.0, whereas it reached 63 mgO 2 /dm 3 in the non-pre-treated sludge. A rapid decrease in temperature directly affects the external and internal cellular structures of microorganisms.…”
Section: Stagementioning
confidence: 95%
“…(2019) [34], the COD content in the dissolved phase increased to 205 mgO 2 /dm 3 at a SCO 2 /SAS volumetric ratio of 0.25 and peaked at 889 mgO 2 /dm 3 at a SCO 2 /SAS ratio of 1.0, whereas it reached 63 mgO 2 /dm 3 in the non-pre-treated sludge. A rapid decrease in temperature directly affects the external and internal cellular structures of microorganisms.…”
Section: Stagementioning
confidence: 95%
“…Almost double increase in the concentration of dissolved COD was demonstrated by Stabnikova et al (2008) in their study on the effect of the freezing/defrosting process on food waste [48], and by Örmeci and Vesilind (2001) in their research with sewage sludge from the North Durham Wastewater Treatment Facility, Durham, NC [49]. In turn, Machnicka et al (2019) observed a dependency between SCDO dose and the amount of COD released to the supernatant. The SCDO disintegration at the waste-activated sludge (WAS) to SCDO volumetric ratio reaching 1:0.25 led to an increase in COD concentration from the initial value of 63 mgO 2 •dm −3 (crude sludge) to 205 mgO 2 •dm −3 .…”
Section: Resultsmentioning
confidence: 93%
“…The SCDO disintegration at the waste-activated sludge (WAS) to SCDO volumetric ratio reaching 1:0.25 led to an increase in COD concentration from the initial value of 63 mgO 2 •dm −3 (crude sludge) to 205 mgO 2 •dm −3 . Increasing the SCDO/WAS ratio to 1:1 increased COD concentration to 889 mg mgO 2 •dm −3 [39].…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, several factors depend on the destruction of microbes in WAS, such as chemical composition, freezing time, freezing temperature, and the rate of freezing. This method helps in dissociating floc structure and cells by forming ice crystals surrounding the cell walls, increasing the cytoplasmic water content and damaging the cell wall by osmotic shock, decreasing the strength of RNA and DNA, and thereby inducing cold death of microorganisms (Machnicka et al, 2019). A study by Kazimierowicz et al (2021) revealed that the chemical oxygen demand enhanced to 490.6 ± 12.3 mg dm −3 when the dry ice to WAS ratio was .3.…”
Section: Innovative Techniquesmentioning
confidence: 99%